(untitled) (Chittagong University Journal of Biological Sciences, 2024)
Properties of some soils of banana, jackfruit and pineapple orchards of different locations in the Chittagong Hill Tracts were studied. Soil samples were analyzed for particle size distribution,texture,pH,organic matter,total nitrogen, available P and 1N NH4OAc extractable K+,Ca2+and Mg2+. Particle size distributions were 76-87% sand,2-12% silt and 10-15% clay. The textural classes of the soils varied from loamy sand to sandy loam.Soil pH,organic matter,total N and available P varied from 4.62 to 5.47,1.66 to 2.58%,0.11 to 0.18%,and 0.48 to 5.56 mg kg-1,respectively. These properties varied significantly within the sites in all types of orchard except total N in pineapple orchard. 1N NH4OAc extractable K+,Ca2+ and Mg2+ ranged from 0.20 to 0.69 cmol kg-1,2.00 to 3.18 cmol kg-1 and 0.72 to 1.61 cmol kg-1,respectively. A significant variation in exchangeable K+,Ca2+ and Mg2+was observed among the sitesin all types of orchard. The Chittagong Univ. J. B. Sci. 9(1&2):89-98,2019